Recombinant Expression of Serratia marcescens Outer Membrane Phospholipase A (A1) in Pichia pastoris and Immobilization With Graphene Oxide-Based Fe3O4 Nanoparticles for Rapeseed Oil Degumming - Yang, Peizhou; Jiang, Suwei; Wu, Yun; Hou, Zhigang; Zheng, Zhi; Cao, Lili; Du, Mingrui; Jiang, Shaotong (Frontiers in Microbiology, 2019)
Enzymatic degumming is an effective approach to produce nutritional, safe, and healthy refined oil. However, the high cost and low efficiency of phospholipase limit the application of enzymatic degumming. In this study, an 879 bp outer membrane phospholipase A (A1) (OM-PLA1) gene encoding 292 amino acid residues was isolated from the genome of Serratia marcescens. The recombinant OM-PLA1 profile of appropriately 33 KDa was expressed by the engineered Pichia pastoris GS115. The OM-PLA1 activity was 21.2 U/mL with the induction of 1 mM methanol for 72 h. The expression efficiencies of OM-PLA1 were 0.29 U/mL/h and 1.06 U/mL/OD600. A complex of magnetic graphene oxide and OM-PLA1 (MGO-OM-PLA1) was prepared by immobilizing OM-PLA1 with graphene oxide-based Fe3O4 nanoparticles by cross-linking with glutaraldehyde. The content of phosphorus decreased to 5.1 mg/kg rapeseed oil from 55.6 mg/kg rapeseed oil with 0.02% MGO-OM-PLA1 (w/w) at 50 °C for 4 h. MGO-OM-PLA1 retained 51.7% of the initial activity after 13 times of continuous recycling for the enzymatic degumming of rapeseed oil. This study provided an effective approach for the enzymatic degumming of crude vegetable oil by developing a novel phospholipase and improving the degumming technology.